ANALISIS NATURALISASI BERDASARKAN UNDANG-UNDANG NO. 12 TAHUN 2006 TENTANG KEWARGANEGARAAN - Sujud, Mohamad Iqbal (Ensiklopedia of Journal, 2025)
Abstract: Naturalization is the process of changing status from a foreign resident to a citizen of a country. In practice, naturalization can have positive and negative impacts on community life. This study uses a descriptive normative juridical research type. Secondary data is analyzed qualitatively. Concluding using deductive logic. The results of the study indicate that the government needs to implement selective policies to prevent negative impacts that will arise, to support order and security, and to implement selective filtering or screening by the Indonesian government as stated in Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia. This article explains what and how the naturalization process is in various dimensions, as well as some of its legal issues.Keywords: Naturalization, Citizenship, Citizen.